Weakly bound Nuclei - Pakou, A. (HNPS Advances in Nuclear Physics, 2021)
The development of radioactive beam facilities makes possible the study of weakly bound nuclei far from stability and close to the drip lines. A vast variety of nuclei is now available, therefore a new research ground is open for the discovery of phenomena previously unexpected. Complementary studies with stable weakly bound nuclei can assist such studies. Examples for $^6$He and $^6$Li are discussed.